2013
DOI: 10.1261/rna.040097.113
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of activation of elongation factor Tu by ribosome: Catalytic histidine activates GTP by protonation

Abstract: Elongation factor Tu (EF-Tu) is central to prokaryotic protein synthesis as it has the role of delivering amino-acylated tRNAs to the ribosome. Release of EF-Tu, after correct binding of the EF-Tu:aa-tRNA complex to the ribosome, is initiated by GTP hydrolysis. This reaction, whose mechanism is uncertain, is catalyzed by EF-Tu, but requires activation by the ribosome. There have been a number of mechanistic proposals, including those spurred by a recent X-ray crystallographic analysis of a ribosome:EF-Tu:aatRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 41 publications
2
41
1
Order By: Relevance
“…Recent works (14,30) questioned some of the findings in our previous study of EF-Tu′. However, one of those works (14) had Fig.…”
Section: Exploring the Activation Of Ef-tumentioning
confidence: 84%
See 2 more Smart Citations
“…Recent works (14,30) questioned some of the findings in our previous study of EF-Tu′. However, one of those works (14) had Fig.…”
Section: Exploring the Activation Of Ef-tumentioning
confidence: 84%
“…Although we repeatedly addressed the risk in the assumption that just running QM/MM calculations should give the correct result to major biological problems, we find it useful to discuss here as an example of a recent work on EF-Tu′ (14). As stated in section Exploring the Activation of EF-Tu, this work concluded that the barrier for the 1W mechanism in EF-Tu′ is around 50 kcal/mol, not recognizing that obtaining the 1W barrier in water is already far above the ability of what is in some respects a minimization-type mapping that does not attempt to produce any 2D surface of the type obtained in the careful study of ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations of H84 strongly affect the GTPase activity of the factor (5,7,(27)(28)(29). Several recent theoretical studies on the mechanism of GTP hydrolysis of EF-Tu (13,27,(29)(30)(31) have Significance Translational elongation factor Tu (EF-Tu) utilizes GTP hydrolysis to control the speed and fidelity of decoding. We explored the reaction coordinate for GTP hydrolysis by EF-Tu and the origins of the million-fold activation effect of the ribosome.…”
mentioning
confidence: 99%
“…Several models have been proposed for the mechanism of GTP hydrolysis by EF-Tu and other GTPases based on structural, theoretical and biochemical studies. 20,[53][54][55][56][57][58][59][60][61][62] In general, the reaction proceeds through a nucleophilic attack of a water molecule on the c-phosphate of GTP. For the reaction to become efficient, the water molecule has to be activated.…”
Section: Multiple Pathways Of Gtp Hydrolysismentioning
confidence: 99%